2023
DOI: 10.1007/s10750-023-05268-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear genome annotation of wheel animals and thorny-headed worms: inferences about the last common ancestor of Syndermata (Rotifera s.l.)

Abstract: The basal splits within Syndermata probably date back hundreds of millions of years, and extant syndermatans greatly differ in reproduction modes (parthenogenesis, metagenesis, heterosexuality) and lifestyles (free-living, epizoic, endoparasitic). Against this background, the present investigation aims to reconstruct genome and transcriptome metrics in the last common ancestor (LCA) of Syndermata. We especially annotated nuclear genome assemblies of one representative, each, of monogononts (Brachionus plicatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…This revealed that genome size estimates or assembly quality could not explain microRNA losses (Figure 2A, R 2 =0.17 and R 2 =0.08, respectively). Instead, we found a correlation between the number of protein-coding genes (numbers taken from (Hagemann et al 2023)) and microRNA families averaging to 424 protein-coding gene losses per microRNA family loss (R 2 =0.64) (Figure 2B). This suggests that the reduction of protein-coding genes is closely linked to a reduction of microRNA families.…”
Section: Hierarchical Loss Of Protein-coding Genes Reflects Microrna ...mentioning
confidence: 86%
“…This revealed that genome size estimates or assembly quality could not explain microRNA losses (Figure 2A, R 2 =0.17 and R 2 =0.08, respectively). Instead, we found a correlation between the number of protein-coding genes (numbers taken from (Hagemann et al 2023)) and microRNA families averaging to 424 protein-coding gene losses per microRNA family loss (R 2 =0.64) (Figure 2B). This suggests that the reduction of protein-coding genes is closely linked to a reduction of microRNA families.…”
Section: Hierarchical Loss Of Protein-coding Genes Reflects Microrna ...mentioning
confidence: 86%
“…Within the Syndermata (Hagemann et al 2023;Sielaff et al 2015), phylum Rotifera (sensu stricto) comprises a diverse group of micrometazoans that reside in diverse habitats and exhibit a rich array of morphologies and life histories. Within this diversity rotifers do possess common features including a ciliated anterior end, trophi (jaws), an intracytoplasmic lamina (ICL) Wallace et al 2015).…”
Section: Introductionmentioning
confidence: 99%